Macroeconomic and distributional impacts of jatropha based biodiesel in Mali - Dorothée Boccanfuso; Massa Coulibaly; Luc Savard; Govinda Timilsina (Economies, 2018)
Mali has introduced a program to produce biodiesel using jatropha, a shrub widely available throughout the country. The aim of the program is to partially substitute diesel, which is entirely supplied through imports, with domestically produced biodiesel. In this paper, we use a computable general equilibrium (CGE) model and a microsimulation model to analyze macroeconomic and distributional impact of a hypothetical expansion of jatropha based biodiesel industry in Mali. We find that the expansion of biodiesel industry (i.e., both jatropha farming and oil conversion), would increase GDP, though slightly, if idle lands are utilized for jatropha cultivation. However, the expansion of jatropha would cause slight loss in GDP if the existing agriculture land is used for jatropha cultivation. The distributional results are slightly different. We find that rural poverty would decrease no matter whether idle lands or existing agricultural lands are used for jatropha plantation, although the percentage reductions in rural poverty are higher in the former compared to the latter case. Our results indicate that if governments plan to promote jatropha biodiesel they should not allow jatropha to compete with food staples on the existing land. Policies should be targeted to utilize the idle lands which have not been used for any productive use.
Keywords: D58; D31; I32; Q17; 330; biofuels; agriculture; computable general equilibrium model; micro-simulation; distributional analysis